2012
DOI: 10.1128/aem.01103-12
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Production of Caffeic Acid by Bacterial Cytochrome P450 CYP199A2

Abstract: ABSTRACTCaffeic acid is a biologically active molecule that has various beneficial properties, including antioxidant, anticancer, and anti-inflammatory activities. In this study, we explored the catalytic potential of a bacterial cytochrome P450, CYP199A2, for the biotechnological production of caffeic acid. When the CYP199A2 enzyme was reacted withp-coumaric acid, it stoichiometrically produced caffeic acid. The crystal structure of CYP199A2 shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Additionally, riboflavin (1 mM) was added for enhanced metabolism, 5-aminolevulinic acid (1 mM) for enhanced heme synthesis, and FeCl 3 (0.25 mM) for increased CYP and Fd functionality (i.e. supplying iron for the CYP heme and Fd) 56 . Substrates were incubated for three days in the cultures while shaken at 30 °C and 225 RPM.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, riboflavin (1 mM) was added for enhanced metabolism, 5-aminolevulinic acid (1 mM) for enhanced heme synthesis, and FeCl 3 (0.25 mM) for increased CYP and Fd functionality (i.e. supplying iron for the CYP heme and Fd) 56 . Substrates were incubated for three days in the cultures while shaken at 30 °C and 225 RPM.…”
Section: Methodsmentioning
confidence: 99%
“…[1,17,19,21,32] In order to investigate the whole-cell turnover of these substrates, we utilised a system developed in our laboratory which produced CYP199A4, HaPux and HaPuR in E. coli. [1] Using low cell density cultures (3 g cell wet weight.L 1 ), we have shown that 4-methoxybenzoic acid was rapidly converted to 4-hydroxybenzoic acid with 2 mM substrate being completely turned over in less than 4 hours and 4 mM in 24 hours (Fig.…”
Section: Whole-cell Oxidation Turnover Assaysmentioning
confidence: 99%
“…In the last years, several studies have used the enzymes involved in the phenylpropanoid pathway to produce compounds other than curcuminoids, such as phenylpropanoic acids (coumaric acid, caffeic acid, and ferulic acid) (140,141,151,152,(154)(155)(156)(157), stilbenoids (155,158), and flavonoids (116,117,150,155,(159)(160)(161)(162). In the design and construction of those pathways, some enzymes from other organisms were used that could also be considered for the optimization of the heterologous production of curcuminoids.…”
Section: Figmentioning
confidence: 99%
“…Furuya et al (156) found that Rhodopseudomonas palustris cytochrome P450 CYP199A2 possesses hydroxylation activity toward p-coumaric acid (and cinnamic acid) and subjected it to site-directed mutagenesis to create mutants with novel and improved catalytic properties. E. coli coexpressed CYP199A2 with the redox partners' putidaredoxin reductase (pdr) from Pseudomonas putida and palustrisredoxin (pux) from R. palustris.…”
Section: Figmentioning
confidence: 99%